38. STUDY ON THE EFFECTIVENESS OF QUADRATUS LUMBORUM BLOCK COMBINED WITH INTRAVENOUS DEXAMETHASONE VERSUS INTRATHECAL MORPHINE FOR POST-CAESAREAN ANALGESIA (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of quadratus lumborum block combined with intravenous Dexamethasone compared to intrathecal Morphine for pain control after ceasarean section.Subjects and Methods: This was a randomized comparative study involving 130 parturients undergoing caesarean section with spinal anesthesia, conducted from May 2023 to June 2024.Results: VAS scores at rest and during movement from the 4th to 24th hour were significantly higher in the group receiving QBL combined with intravenous Dexamethasone compared to the ITM group. The incidence of side effects was also significantly lower in the QBL+ Dexamethasone group (9.2%) compared to the ITM group (43.1%).Conclusion: Postoperative pain relief duration was lower and side effect rates were lower in the group receiving quadratus lumborum block combined with intravenous Dexamethasone compared to the intrathecal Morphine group.
Keywords: Intrathecal Morphine, quadratus lumborum block, postoperative pain relief after cesarean section.